Diversity of rove beetles (Coleoptera, Staphylinidae) in restored high-Andean forests from the Colombian Central Andes - MÉNDEZ-ROJAS, DIANA M.; LÓPEZ-GARCÍA, MARGARITA M.; GARCÍA-CÁRDENAS, ROCÍO (Revista Colombiana de Entomología, 2012)
Rove beetle diversity in Colombia is still scarce and even more in high mountain ecosystems which are one of the most vulnerable habitats. So, community diversity of these insects was studied in a high-Andean landscape on the Colombian Central Andes, which is being ecologically restored. Pasture, forest plantation, regenerating forest plantation, secondary forest and mature secondary forest, were chosen by using environmental and vegetation features. In each landscape element, a linear transect was defined applying Winkler bags and carriontraps as collecting methods. Abundance, richness and community structure were compared between habitats. In order to correlate environmental variables with richness of staphylinids, a multiple correlation was carried out. A non-metrical multidimensional scaling analysis based on species composition was made for landscape elements. Complementarity Index was used as beta diversity measure. 3,065 specimens representing, 11 subfamilies, 34 genera and 122 morphospecies were collected. Alfa diversity between landscape elements was statistically different, being higher for sites with higher regeneration. Staphylinid abundance and richness were negatively correlated with soil temperature and positively with arboreal coverage percentage. Although species composition was statistically different between elements, a separation between secondary forest and regenerating plantation was not found. The high beta diversity values made evident the importance of highAndean landscapes for biological conservation.